2015
DOI: 10.14483/udistrital.jour.calj.2015.2.a05
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating vocabulary learning through metacognitive strategy training and learning journals

Abstract: Promoción del aprendizaje de vocabulario a través del entrenamiento en estrategias metacognitivas y diarios de aprendizaje AbstractThis paper reports on a mixed-method action research study carried out with participants from three public high schools in different regions in Colombia: Bogotá, Orito, and Tocaima. The overall aim of this study was to analyze whether training in the use of metacognitive strategies (MS) through learning journals could improve the participants' vocabulary learning. The data, collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…The results indicate that participants generally have a clear goal in their vocabulary learning. Trujillo Becerra et al (2015) reported similar findings concluding that goal-setting strategies employed in vocabulary learning also brough about improvements in self-directed learning. However, items related to awareness of planning, deadlines, difficulties, and seeking feedback from teachers and peers had significantly lower means (p < 0.001), suggesting that participants may face challenges in these areas and need to improve their planning, problemsolving, implementation, and adaptability skills which is supported by other studies (Chamot, 2004;Saengpakdeejit, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…The results indicate that participants generally have a clear goal in their vocabulary learning. Trujillo Becerra et al (2015) reported similar findings concluding that goal-setting strategies employed in vocabulary learning also brough about improvements in self-directed learning. However, items related to awareness of planning, deadlines, difficulties, and seeking feedback from teachers and peers had significantly lower means (p < 0.001), suggesting that participants may face challenges in these areas and need to improve their planning, problemsolving, implementation, and adaptability skills which is supported by other studies (Chamot, 2004;Saengpakdeejit, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…Metacognition is represented in what a student knows about themselves as a learner and has been conceptualised as a blend of knowledge and regulation (Flavell, 1979). Students' knowledge about learning strategies and the ways they monitor, plan, and evaluate their learning (Trujillo-Becerra et al, 2015) are also aspects of metacognition. The coding procedures revealed that participants managed their learning through three metacognitive strategies: monitoring learning, implementing speaking strategies, and using assessment methods.…”
Section: Exhibition Of Self-regulated Behavioursmentioning
confidence: 99%
“…In the examined data, all teachers referred to plan, taking into consideration contextual issues that help students analyze daily situations especially in regard to the environment. According to Trujillo Becerra, Alvarez Ayure, Zamudio Ordoñez, and Morales Bohórquez (2015), and Mendieta Aguilar (2009) this denotes an increasing interest for teachers to plan their classes with a premise of more real contexts activities. These also lead to enriched comprehension for students in that lifelong learning connections are built, and knowledge is expanded based on inquiry processes.…”
Section: Planning and Implementating With A Contextual Focus In Mindmentioning
confidence: 99%